The Effect of Warm Water Compresses on the Intensity of Dysmenorrhea Pain Scale Among Adolescents at Nusantara Private Senior High School, Lubuk Pakam - Ika Nur Saputri; Isma Eliza Hasibuan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Dysmenorrhea is a menstrual pain condition commonly experienced by adolescent girls, often interfering with daily activities both in school and social environments. The high prevalence of dysmenorrhea makes it one of the reproductive health issues that requires attention, particularly among adolescents. Management of dysmenorrhea can be carried out through pharmacological and non-pharmacological approaches. One of the non-pharmacological methods that is simple, inexpensive, and easy to apply is warm water compress therapy. The mechanism of warm compresses involves vasodilation of blood vessels, improved blood circulation, muscle relaxation, and reduction of pain perception, making it effective in alleviating dysmenorrhea symptoms. This study aimed to determine the effect of warm water compresses on the intensity of dysmenorrhea pain among adolescent girls at Nusantara Private Senior High School, Lubuk Pakam. The research design was pre-experimental using a one-group pretest–posttest approach. A total of 19 respondents were selected using purposive sampling. Data were analyzed using the Wilcoxon test. The results showed a significant reduction in pain intensity after the intervention, with Z = -3.873 and p-value = 0.000 (p < 0.05). The mean pain scale decreased from 2.68 to 1.89. It can be concluded that warm water compress therapy is effective in reducing the intensity of dysmenorrhea pain among adolescent girls. These findings suggest that warm compresses may serve as a recommended non-pharmacological nursing intervention to alleviate menstrual pain in adolescents.